RP-HPLC analysis of phenolic compounds and flavonoids in beverages and plant extracts using a CoulArray detector - Jandera, Pavel; Skeifíková, Veronika; Rehová, Lucie; Hájek, Tomás; Baldriánová, Lucie; Skopová, Gabriela; Kellner, Vladimír; Horna, Ales (Journal of separation science, 2005)
Methods were developed for the analysis of natural antioxidants including phenolic compounds and flavonoids in beverages and plant extracts using gradient HPLC with multi-channel electrochemical coulometric detection. Suitability of various reversed-phase columns for this purpose was compared; pH and mobile phase gradients were optimized with respect to the separation selectivity and sensitivity of detection. Because of different target compounds in various sample types, the overlapping resolution maps and the normalized resolution product approaches described earlier were used to select optimum columns and gradients to suit the analysis of the individual sample types. The methods were applied to the analysis of phenolic compounds and flavonoids in beer, wine, tea, and yacon extracts. 32 phenolic compounds were identified and determined, including derivatives of benzoic and cinnamic acids, flavones, and a few related glycosides. Eight-channel CoulArray detection offers high selectivity and sensitivity with limits of detection in the low microg L(-1) range, at least an order of magnitude lower than single-channel coulometric detection using the Coulochem detector. No special sample pretreatment is necessary and, because of the compatibility of the CoulArray detector with gradient elution, phenolic antioxidants of different polarities can be determined in a single run. In addition to the retention times, the ratios of the areas of the pre-dominant and post-dominant peaks to the area of the dominant peak can be used for improved identification of natural antioxidants.
Keywords: flavonoidy; Phenols; Beverages; Chromatography, High Pressure Liquid; Reference Standards; Flavonoids; Electrochemistry; Plant Extracts; Sensitivity and Specificity; senzitivita a specificita; nápoje; fenoly; elektrochemie; referenční standardy; vysokoúčinná kapalinová chromatografie; rostlinné extrakty